Investigating the moderating effect of social media on the relationship between brand architecture and brand love among telecommunication service provider users - Al Amirul Eimer Ramdzan Ali; Asmaul Husna Haris Fadzilah; Syahrul Nizam Salam; Nur Aqilah Hazirah Mohd Anim; Muhammad Fairuz bin Jamil; Amalina Mursidi; Mohd Safwan Ramli (Islamic Azad University, 2024)
Branding can be defined as a set of tangible and intangible attributes that are designed to create awareness and identity, with the aim to build the reputation of a product, service, person, place and organization. In order to ensure that the customers are in “love” with the brand, organizations, particularly telecommunication service providers must consider the branding architecture which focuses on three (3) main dimensions: branded house, stand-alone and brand endorsement. Therefore, the objective of this study is to investigate the moderating role of social media towards brand architecture and brand love with Resource Based View as fundamental theory. Using quantitative methodology, this study involved 420 respondents from five different brands of telco users. The implications of this research are telecommunication service providers need to consider each component of branding architecture to ensure long-term business operation and that the outcome of this research will also provide additional insight into business sustainability model. Theoretical and practical implications were discussed to provide insights for future research in this area.